KONSEP HALALAN THAYYIBAN DALAM AL-QUR’AN SURAH AL-BAQARAH AYAT 168: ANALISIS KOMPARATIF TAFSIR AL-AZHAR DAN TAFSIR AL-MISBAH - Ahmad Al Tasdiq; Yeti Dahliana (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2025)
Islam provides comprehensive regulations for human actions in fulfilling life’s necessities, particularly in the consumption of food and beverages, ensuring that they are obtained lawfully (halal) and bring blessings. This principle is emphasized in Surah Al-Baqarah verse 168, which commands humankind to consume halalan thayyiban and to avoid following the footsteps of Satan. This study aims to analyze the concept of halalan thayyiban through a comparative study of two authoritative Indonesian exegeses: Tafsir Al-Azhar by Prof. Dr. Haji Abdulmalik Abdulkarim Amrullah (HAMKA) and Tafsir Al-Misbah by M. Quraish Shihab. The research employs a library research method with a qualitative approach and descriptive-textual analysis. Primary sources consist of the Qur’an, Tafsir Al-Azhar, and Tafsir Al-Misbah, while secondary sources include journals, books, and relevant scholarly literature. The findings reveal that HAMKA interprets lawful food as the opposite of prohibited ones explicitly mentioned in the Qur’an, namely carrion, blood, pork, and sacrifices offered to idols. Meanwhile, Quraish Shihab emphasizes that lawful food refers to what is not forbidden, either by its substance or by the manner of its acquisition. Both scholars agree that not everything lawful is automatically thayyib, as goodness is also determined by cleanliness, health, and the ethical means of obtaining it. Thus, the concept of halalan thayyiban extends beyond the legal status of permissibility, encompassing moral values, hygiene, health, and blessings that contribute to the spiritual and social well-being of Muslims.